Bearing witness : stories of the Holocaust - McCampbell, Darlene Z.; Rochman, Hazel (Orchard Books, 1995)
Offers a multifaceted view of the Holocaust, from a child's bewilderment at having to wear a star and later go into hiding, to the agony of the camps themselves.